The Role of Education: Building Student Entrepreneurship Character Through Green Economic - Sucipto; Jaya, Fitra; Sultan, Zulkifli; Puspitaningsih, Flora; Mukhtar, Afiah; D. Hadji Latif, Sahraman (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2025)
Entrepreneurship education plays a role in supporting the green economy by developing students who are innovative, independent, and socially responsible. These traits are essential for fostering sustainable business practices, innovation drives the creation of environmentally friendly solutions, independence drives proactive action in addressing environmental challenges, and social responsibility ensures appropriate decision-making with long term ecological impacts. This study examines the effect of a project-based learning model that integrates entrepreneurship and environmental desires on students' entrepreneurial character. Using a quantitative approach, data were collected from 400 high school students in East Java and analysed using Structural Equation Modelling (SEM) using AMOS. The findings indicate that education significantly increases awareness of green economy principles and supports students' entrepreneurship. However, although entrepreneurial character is positively associated with students' entrepreneurship, the relationship is not statistically significant. Similarly, the green economy contributes to character development, although its direct impact on entrepreneurship is also insignificant. These results highlight the importance of instilling green economy principles in entrepreneurship education as a foundation for building a generation of entrepreneurs committed to innovation, independence, and environmental responsibility.